Multi-Hazard Assessment of RC Bridges using Unmanned Aerial Vehicle-Based Measurements - Orkan Özcan; Okan Özcan (The Baltic Journal of Road and Bridge Engineering)
The structural performance of reinforced concrete bridges is crucial regarding the bridge safety. Monitoring the bridge performance under multihazard effects such as scour, and earthquake becomes even more important. Thus, the scour depth along the piers and piles of bridge substructures has to be measured and tracked consistently in order for reliable multi-hazard bridge behaviour predictions. A practical Unmanned Aerial Vehicle based scour measurement method was proposed to increase the measurement accuracy and reduce the implementation costs. This method has been used in shallow and clear-water riverbeds. The Boğaçayı Bridge was selected as the case study located at the Boğaçayı River in Antalya, Turkey, since it was exposed to stream and flood, induced scour in the previous years. In the study region, the amount of scour was determined with considerable accuracy, and the scour measurements were used for generating the Three-Dimensional Finite Element model of the bridge. The multi-hazard performance of the bridge was acquired by implementing nonlinear static analysis using pushover curves corresponding to various scour depths concentrated at some of the bridge piers. Therefore, a continuously updateable multi-hazard bridge assessment system was proposed, which was implemented in bridges under scour and earthquake effects, regarding Unmanned Aerial Vehicle based measurements.